ANALISIS MULTIPLIER EFFECT PAJAK, INVESTASI DAN PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI KALIMANTAN TIMUR - Erni Setiawati; Rudy Syafariansyah Dachlan; Lita Furiawan; Karin Setiani; Herdi Nirwany (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2019)
Abstract. This study aims to measure the magnitude of the multiplier number coefficient (multiplier effect coefficient) tax, investment and government expenditure and its impact on the economic growth of East Kalimantan Province. The data sources used are secondary data derived from publication data by the Central Statistics Agency (BPS) of Province at East Kalimantan This type of research is quantitative descriptive. The analytical method uses the Economic Balance equation model, namely Y = C + I + G with a Multiplier Effect Coefficient analysis, which consists of a tax multiplier (kT), investment multiplier (kI) and government expenditure multiplier (kG). The observed / measured variables are the level of GDP, the level of household consumption, the total investment value of both the private sector and the government, and the amount of government expenditure.